DISIPLIN KERJA DALAM ISLAM - Abdullah, Wahidah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
Work Discipline is one of the keys to success. Success is the right of every person who discipline in work . Discipline makes things orderly . If everything has been organized , then whatever work we do will be the responsibility and the mandate will be expected to achieve its full potential . the work carried out by the discipline and intentions are sincere and honest to the common good (kemslahatan) would be worth worship as a form of good deeds. Relative to the religion of Islam as a universal religion , not only regulates human life from the aspect of worship , but also regulate all aspects of human life in order to achieve success and happiness in this world and the hereafter. everything in relation to worship has been set out clearly in Islam , so that a Muslim is required to execute them according worship religious guidance . So that, the discipline is something that is a priority in Islam . These can then be applied in the world of work where we are.